Pressure-selective modulation of NMDA receptor subtypes may reflect 3D structural differences - Mor, Amir; Kuttner, Yosef Y.; Levy, Shiri; Merav, Mor; Hollmann, Michael; Grossman, Yoram (Frontiers in Cellular Neuroscience, 2012)
Professional deep-water divers exposed to high pressure (HP) above 1.1 MPa suffer from High Pressure Neurological Syndrome (HPNS), which is associated with CNS hyperexcitability. We have previously reported that HP augments N-methyl-D-aspartate receptor (NMDAR) synaptic responses, increases neuronal excitability, and potentially causes irreversible neuronal damage. We now report that HP (10.1 MPa) differentially affects eight specific NMDAR subtypes. GluN1(1a or 1b) was co-expressed with one of the four GluN2(A-D) subunits in Xenopus laevis oocytes. HP increased ionic currents (measured by two electrode voltage clamps) of one subtype, reduced the current in four others, and did not affect the current in the remaining three. 3D theoretical modeling was aimed at revealing specific receptor domains involved with HP selectivity. In light of the information on the CNS spatial distribution of the different NMDAR subtypes, we conclude that the NMDAR’s diverse responses to HP may lead to selective HP effects on different brain regions. These discoveries call for further and more specific investigation of deleterious HP effects and suggest the need for a re-evaluation of deep-diving safety guidelines.